Cooperación descentralizada y la gestión de los gobiernos autónomos descentralizados en el Ecuador - Gallardo Sánchez, María Alejandra (2015)
The study evaluated the management of international cooperation by different levels of the autonomous governments and institutional capacities applied based on the Five Principles of Paris, according to the competences of each GAD after resolution 0009-CNC-2011. The resolution was published on 29th September on 2011 by the National Council of competencies in Guayaquil which decentralizes and transfers the jurisdiction of the International Cooperation to different levels of Autonomous Decentralized Governments: Provincial, Municipal and Parish (GAD). An analytical review of the concepts and evolution of international cooperation was conducted. Rules of cooperation of Ecuador that GAD apply in the cooperation management was examined. Finally, a quantitative investigation of the amount of resources for international cooperation implemented by GAD was developed and it was concluded with an analytical comparison of cooperation management based on institutional capacities applied by GAD through surveys to three technical commissioned in international cooperation in each GAD level…